The Case of Lionfish (Pterois miles) in the Mediterranean Sea Demonstrates Limitations in EU Legislation to Address Marine Biological Invasions - Periklis Kleitou; Jason M. Hall-Spencer; Ioannis Savva; Demetris Kletou; Margarita Hadjistylli; Ernesto Azzurro; Stelios Katsanevakis; Charalampos Antoniou; Louis Hadjioannou; Niki Chartosia; Maria Christou; Yiannis Christodoulides; et al. (Journal of Marine Science and Engineering, 2021)
The European Regulation (EU) 1143/2014 on Invasive Alien Species entered into force in 2015, with the aim to fulfill regional and international biodiversity goals in a concerted manner. To date, the Regulation listed 66 Invasive Alien Species (IAS) that are subject to legal controls. Only one of these is marine. A recent lionfish (Pterois miles) invasion has been closely monitored in the Mediterranean and a detailed risk assessment was made about the profound impacts that this invasive fish is likely to have on the fisheries and biodiversity of the region. In 2016–21, lionfish rapidly became dominant predators along Eastern Mediterranean coasts, yet the process for their inclusion on the EU IAS list has been lengthy and is ongoing. There is an urgent need to learn from this experience. Here, we recommend improvements to the Regulation 1143/2014 and the risk assessment process to protect marine ecosystems and secure the jobs of people that rely on coastal resources.